Quercetin modulates liver response to circadian rhythm disturbance and γ-radiation in rats: oxidant-antioxidant status and ATP production - Amal K. Omar; Nahed Abdel-Aziz; Hoda G. Hegazy; Safaa A. A. El-Seifi (Egyptian Liver Journal)
Abstract Background The mammalian circadian rhythm is an internal biological timekeeping system synchronizing physiology and behavior to light/dark cycles. Several processes throughout the body’s organs, including the liver, are regulated by circadian rhythms and are adversely affected by radiation exposure. This study investigates the effect of circadian rhythms, whether it is regular (light/darkness cycle) or disturbed (permanent darkness or permanent light), under the stress of whole-body irradiation, and the possible protective impact of quercetin on certain liver aspects. Methods The animals were divided into three main groups: a normal light/dark group, a permanent darkness group, and a permanent light group. Each group was subdivided into four subgroups: a control subgroup (nonirradiated rats), an irradiated subgroup (exposed to 9-Gy fractionated dose), a quercetin subgroup (received 50 mg/kg b.wt. of quercetin for 1 month), and a quercetin + irradiated subgroup. Results The results showed that circadian rhythm disturbance and/or whole-body irradiation-induced oxidative stress, as indicated by elevation of liver MDA and NO, was associated with decreases in antioxidant enzymes’ activities (SOD, GPx, and CAT) and GSH contents, compared to the corresponding control subgroups. This was also accompanied by a disruption in mitochondrial function, as indicated by increased cytochrome P450 reductase and decreased ATP levels. ADP levels were also affected. Histological investigation of liver tissues showed marked alterations. However, oral administration of quercetin pre- and during irradiation attenuated these changes. Conclusion Oral administration of quercetin could protect the liver from these damaging effects by modulating the oxidant-antioxidant system and ATP production.